Taxonomic revision of Rhynchosia Lour. (Leguminosae, Papilionoideae, Phaseoleae) in South America - Bezerra, Luísa Maria De Paula Alves [UNESP]; Cândido, Elisa Silva; Vargas, Wanderleia D.E.; Torke, Benjamin Marland; Lewis, Gwilym Peter; Perez, Ana Paula Fortuna [UNESP] (Magnolia Press, 2024)
Rhynchosia Lour. has a pantropical distribution and comprises approximately 230 species, of which ca. 55 occur in the Neotropics and 31 in South America. The only existing taxonomic review that treated the South American species of the genus was carried out in 1978. It does not account for many new collections and several recently described species, and the delimitation of taxa remains problematic. Consequently, we undertook a comprehensive review of the South American species of Rhynchosia and present here a new taxonomic revision. The revision is based on our own fieldwork, extensive study of the relevant literature, and analysis of ca. 2000 herbarium collections including the nomenclatural types for all published names that have been linked to the South American taxa of Rhynchosia. Twenty-seven species are recorded for South America, where they are distributed in a variety of open and forested habitats, with the greatest diversity concentrated in the Cerrado domain. Most of the South American taxa are widely distributed in this region and some also occur in Central and North America. Rhynchosia minima is the only species in South America with a larger distribution that extends to the Old World. We provide an identification key, morphological descriptions for all of the recorded taxa, information about the nomenclatural types, synonyms, geographical distributions, habitats, phenology, and conservation status, as well as distribution maps, illustrations and photos of selected species in the field. We present six new synonymizations and 50 lectotypifications, of which 30 are second-step.
Keywords: Cajaninae; diversity; Fabaceae; Neotropics